Legislative Regulation of Territorial and Organizational Foundations of Local Government in the Villages of the Republic of Türkiye - A. G. Bykova (Сибирское юридическое обозрение, 2024)
The study focuses on analyzing Turkish national legislation regarding the territorial and administrative structure of local governance. The relevance of this research stems from the limited exploration of this subject within domestic legal studies. This article is based on the national Turkish legislation, presented in the Author’s translation. The Author describes the legal framework governing local government in Türkiye’s villages, with particular emphasis on the structure and organization of local governance. The analysis of local government legislation was conducted to achieve several aims: first, to identify the territorial structure of local governance; second, to define the local governance system at the lowest level of public authority, specifically in villages; and third, to clarify the legislative delineation of the roles and responsibilities of local governance bodies and officials. The study explores both the foundational and evolving territorial and administrative principles underpinning local governance in Türkiye, highlighting their resilience and effectiveness, which have endured for over a century. The article draws attention to attempts at reforming these territorial and administrative foundations in line with Türkiye’s broader state development goals. The Author employs general, specialized, and specific scientific methods, including formal-logical, historical-legal, analysis and synthesis, abstraction, and problem-chronological methods, to provide a comprehensive overview of Turkish legislation, examine its evolution, and draw conclusions. Notably, the study identifies a direct correlation between the issues facing rural municipalities and Türkiye’s territorial governance structure, which is, in turn, shaped by the country’s administrative-territorial organization. An analysis of Türkiye’s local governance system throughout the 20th and early 21st centuries illustrates a hybrid model of local governance.